Urban Infrastructures & Environmental Risk in Medieval England. (2nd January 2023) - Magnusson, Roberta J.
ABSTRACT: Medieval city walls, bridges, and harbours stood at the interface between the worlds of man and nature. Wind, ice, rainwater, scour, tidal flows, littoral drift, erosion, silting, micro-organisms, and the growth of vegetation compromised the integrity of structural fabrics and choked up ditches, rivers, and harbour basins. These 'slow disasters' of incremental degradation were periodically punctuated by 'fast disasters' such as devastating floods or violent gales. To keep their public works from falling into ruin, civic authorities had to devise regular maintenance regimes and tackle intermittent large-scale repairs. Infrastructure sustainability became a particularly acute problem during the late middle ages. Climate change accelerated the intensity and frequency of environmental stressors, while urban populations declined in the wake of the Black Death. Economic disruptions were driving up the costs of building materials and labour while the customary sources of infrastructure incomes were shrinking. The growing mismatch in scale between rising infrastructure costs and falling resources was not just another wobble that could be corrected by a renewed mobilisation of traditional recovery mechanisms.